1971
DOI: 10.1029/jc076i003p00646
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distributions of radioactivity and89Sr/90Sr ratios during rainstorms

Abstract: Radionuciide concentrations for 89Sr, 90Sr, 144Ce, and 137Cs were sequentially sampled from two rainstorms to study fallout behavior as a function of rainfall rate and type of storm approximately 7 months after the eighth Chinese nuclear explosion of December 27, 1968. Great time variability in the 89Sr/90Sr ratio was found in conjunction with a well‐developed storm on July 21, but a nearly steady ratio was observed in a stratified stable‐type storm on August 14. Tapping of stratospheric air appeared to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
(7 reference statements)
1
4
0
Order By: Relevance
“…After the first 2 months, it is more difficult to interpret the variations in the ratio. It appears that stratospheric tapping by intense thunderstorms may cause a dec{ease in the 9xY/89Sr ratio [Dingle, 1965;Noyce et al, 1971]. It is perhaps more likely that downward intrusions of stratospheric air masses into the troposphere in the Arkansas area via Danielsen 'tropopause folding mechanism' [Danielsen, 1964[Danielsen, , 1968Reed, 1955;Reed and Danielsen, 1959] The data of Thein et al [1968] seem to be in line with our recent data and can be interpreted in a similar manner.…”
supporting
confidence: 87%
“…After the first 2 months, it is more difficult to interpret the variations in the ratio. It appears that stratospheric tapping by intense thunderstorms may cause a dec{ease in the 9xY/89Sr ratio [Dingle, 1965;Noyce et al, 1971]. It is perhaps more likely that downward intrusions of stratospheric air masses into the troposphere in the Arkansas area via Danielsen 'tropopause folding mechanism' [Danielsen, 1964[Danielsen, , 1968Reed, 1955;Reed and Danielsen, 1959] The data of Thein et al [1968] seem to be in line with our recent data and can be interpreted in a similar manner.…”
supporting
confidence: 87%
“…Mid-latitude folding of the tropopause in spring has also been shown to enhance stratospheric-tropospheric exchange of 7 Be and increase 7 Be concentrations in the troposphere (Burchfield et al, 1983;Doering and Akber, 2008;Feely et al, 1989;Heikkila et al, 2008;Noyce et al, 1971). In addition, high-tapping thundershowers in the spring and summer months, can enhance stratospheric-tropospheric exchange and the washout of 7 Be via precipitation (Burchfield et al, 1983).…”
Section: Seasonal and Annual Variations In The Atmospheric Depositionmentioning
confidence: 95%
“…Maximum mixing between the stratosphere and the troposphere generally occurs in the spring of each year at mid-latitudes, and near-surface air at the middle latitudes generally has higher concentrations of 7 Be at this time (Feely et al 1989). Intense thunderstorms may also mix stratospheric air downward, thus increasing the amount of 7 Be available for scavenging by precipitation (Dingle 1965;Noyce et al 1971). Several authors have suggested that vertical mixing within the troposphere also governs the concentration of 7 Be in rain and near-earth surface air (Feely et al 1989;Baskaran 1995;Durana et al 1996;Dueñas et al 1999).…”
Section: Production and Delivery Of 7 Be To The Earth's Surfacementioning
confidence: 98%